Optimizing Continuous Renal Replacement Therapy with Regional Citrate Anticoagulation: Insights from the ORCA Trial—A Retrospective Study on 10 Years of Practice - Rita Jacobs; Walter Verbrugghe; Jason Bouziotis; Ingrid Baar; Karolien Dams; Annick De Weerdt; Philippe G. Jorens (Life)
(1) Background: Citrate is preferred in continuous renal replacement therapy (CRRT) for critically ill patients because it prolongs filter life and reduces bleeding risks compared to unfractionated heparin (UFH). However, regional citrate anticoagulation (RCA) can lead to acid–base disturbances, citrate accumulation, and overload. This study compares the safety and efficacy of citrate-based CRRT with UFH and no anticoagulation (NA) in acute kidney injury (AKI) patients. (2) Methods: A retrospective analysis was conducted on adult patients (≥18 years) who underwent CRRT from July 2010 to June 2021 in an intensive care unit. (3) Results: Among 829 AKI patients on CRRT: 552 received RCA, 232 UFH, and 45 NA. The RCA group had a longer filter lifespan compared to UFH and NA (56 h [IQR, 24–110] vs. 36.0 h [IQR, 17–63.5] vs. 22 h [IQR, 12–48]; all Padj < 0.001). Bleeding complications were fewer in the RCA group than in the UFH group (median 3 units [IQR, 2–7 units] vs. median 5 units [IQR, 2–12 units]; Padj < 0.001) and fewer in the NA group than in the UFH group (median 3 units [IQR, 1–5 units] vs. 5 units [IQR, 2–12 units]; Padj = 0.03). Metabolic alkalosis was more common in the RCA group (32.5%) compared to the UFH (16.2%) and NA (13.5%) groups, while metabolic acidosis persisted more in the UFH group and NA group (29.1% and 34.6%) by the end of therapy vs. the citrate group (16.8%). ICU mortality was lower in the RCA group (52.7%) compared to the UFH group (63.4%; Padj = 0.02) and NA group (77.8%; Padj = 0.003). (4) Conclusions: Citrate anticoagulation outperforms heparin-based and no anticoagulation in filter patency, potentially leading to better outcomes through improved therapy effectiveness and reduced transfusion needs. However, careful monitoring is crucial to limit potential complications attributable to its use.